156k views
1 vote
Log_6⁡(x+1)+log_6⁡x=1

User Flack
by
6.4k points

2 Answers

4 votes

This is pretty simple once you figure out the trick.

All you have to do is make the args common.

Meaning
log_(6)(x + 1) + log_(6)(x) = 1 is nothing but
log_(6)(x(x + 1)) = 1

Which is nothing but:
log_(6)(x^2 + x) = 1.

Now using the scorpion tail method, this equation can be reframed to being:
6 = x^2 + x. You bring 6 to the other side and it'll become:
x^2 + x - 6 = 0

Factorise it and you get:
(x - 2) * (x + 3)

Henceforth, the solution would be
2 and
-3. :D

User RamblingMad
by
6.3k points
4 votes

Answer:

D. x = 9

Explanation:

edge 2022

User Ran Avnon
by
6.2k points